Development and validation of a nomogram to predict the five-year risk of revascularization for non-culprit lesion progression in STEMI patients after primary PCI - Dai, Feng; Xu, Xianzhi; Zhou, Chunxue; Li, Cheng; Tian, Zhaoxuan; Wang, Zhaokai; Yang, Shuping; Liao, Gege; Shi, Xiangxiang; Wang, Lili; Li, Dongye; Hou, Xiancun; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Acute ST-segment elevation myocardial infarction (STEMI) patients after primary PCI were readmitted for revascularization due to non-culprit lesion (NCL) progression.Objective: To develop and validate a nomogram that can accurately predict the likelihood of NCL progression revascularization in STEMI patients following primary PCI.The study enrolled 1612 STEMI patients after primary PCI in our hospital from June 2009 to June 2018. Patients were randomly divided into training and validation sets in a 7:3 ratio. The independent risk factors were determined by LASSO regression and multivariable logistic regression analysis. Multivariate logistic regression analysis was utilized to develop a nomogram, which was then evaluated for its performance using the concordance statistics, calibration plots, and decision curve analysis (DCA).